Ters yüz sınıf yaklaşımının mühendislik fakültesi öğrencileriyle iki farklı grupta incelenmesi - Akı, Fatma Nur (My University, 2021)
Günümüzde iyi hazırlanmış nitelikli bilimsel videoların çokluğu ve internet erişimine açık olmaları eğitim araştırmacılarını da bu kaynaklardan beslenen yeni uygulama alanları açmaya sevk etmiştir. Bu çevrim içi kaynaklardan yararlanarak zenginleşen uzaktan eğitim faaliyetlerinin yüz-yüze eğitimler ile tamamlanması ve kontrol edilmesi daha sağlıklı olmaktadır. Bu sebeple teknoloji kullanımını, sınıf içi etkileşimi desteklediği, sınıf içi zamanın verimli kullanılmasına imkân verdiği için Ters yüz sınıf yaklaşımı günümüzde tercih edilen öğretim yaklaşımlarından biri haline gelmiştir. Bu yaklaşım ders içerisinde öğretmen tarafından aktarılacak anlama ve hatırlama düzeyinde temel teorik bilgileri öğrencilerin evde kendilerine sunulan dökümanlara ve video derslere çalışarak gelmelerini gerektirmektedir. Böylece sınıf içerisinde uygulama aşamasında öğrenme basamaklarına uygun etkinlikler ile derse devam etme imkânıoluşmaktadır. Sınıf içi zaman içerisinde geleneksel derslerde ödev olarak verilen uygulamalar çözülerek, ders süresi daha verimli kullanılır. Bu yenilikçi yaklaşımın başarılı olabilmesi için eğitim alanında uygulama sonuçlarına dayanan model ve kuramların birlikte geliştirilebilmesi önemlidir. Bu araştırmada özgün bir uygulama alanı olarak bir vakıf üniversitesinin Mühendislik Fakültesi öğrencilerinin katılımı ile iki farklı grup katılımcı ile uygulama gerçekleştirilmiştir. Bu gruplardan birincisi mühendislik eğitiminde temel bir yere sahip standartlaşmış fizik laboratuvarı dersini alan öğrencilerden, ikinci grup ise gönüllük esasına dayalı yaratıcı süreçleri tetikleyen bilimsel araştırma projesi çalışma grubu öğrencilerindenoluşmaktadır. Böylelikle mühendislik eğitiminin formal ve formal olmayan eğitim bağlamındaki iki farklı öğrenci grubunun kendi programlarına entegrasyonuyla gerçekleştirilen Ters yüz sınıf yaklaşımı örneklerinin nitel araştırma teknikleri kullanılarak izlenmesi ve sonuçlarını kuramsal alanda tartışmaya açmak amaçlanmıştır.

Today, the abundance of well-prepared scientific videos and the fact that they are open to internet access have led education researchers to open new application areas that are fed from these sources. It is more succesfull to complete and control distance education activities, which are enriched by using these online resources, with face-to-face lectures. For this reason, the Flipped classroom approach has become one of the preferred teaching approaches today, as it supports the use of technology, in-class interaction and allows efficient use of classroom time. This approach requires the students to come to the documents presented to them at home and to the video lessons by studying the basic theoretical knowledge at the level of comprehension and recall to be conveyed by the teacher during the lesson. Thus, it is possible to continue the lesson with activities suitable for the learning steps in the application phase in the classroom. Class time is used more efficiently by solving the problems given as homework in traditional lessons during inclass time.In order for this innovative approach to be successful, it is important that models and theories based on the results of practice in the field of education can be developed together. In this research, as an original application area, the implementation was carried out with the participation of Engineering students of a foundation university with two different groups of participants.The first of these groups consists of students who take the standardized physics laboratory course, which has a fundamental place in engineering education, and the second group consists of students from the scientific research project study group that triggers creative processes based on volunteerism. Thus, it is aimed to monitor the examples of Flipped Classroom Approach, which is realized by the integration of two different student groups in the context of formal and non-formal education of engineering education into their own xToday, the abundance of well-prepared scientific videos and the fact that they are open to internet access have led education researchers to open new application areas that are fed from these sources. It is more succesfull to complete and control distance education activities, which are enriched by using these online resources, with face-to-face lectures. For this reason, the Flipped classroom approach has become one of the preferred teaching approaches today, as it supports the use of technology, in-class interaction and allows efficient use of classroom time. This approach requires the students to come to the documents presented to them at home and to the video lessons by studying the basic theoretical knowledge at the level of comprehension and recall to be conveyed by the teacher during the lesson. Thus, it is possible to continue the lesson with activities suitable for the learning steps in the application phase in the classroom. Class time is used more Today, the abundance of well-prepared scientific videos and the fact that they are open to internet access have led education researchers to open new application areas that are fed from these sources. It is more succesfull to complete and control distance education activities, which are enriched by using these online resources, with face-to-face lectures. For this reason, the Flipped classroom approach has become one of the preferred teaching approaches today, as it supports the use of technology, in-class interaction and allows efficient use of classroom time. This approach requires the students to come to the documents presented to them at home and to the video lessons by studying the basic theoretical knowledge at the level of comprehension and recall to be conveyed by the teacher during the lesson. Thus, it is possible to continue the lesson with activities suitable for the learning steps in the application phase in the classroom. Class time is used more efficiently by solving the problems given as homework in traditional lessons during inclass time.In order for this innovative approach to be successful, it is important that models and theories based on the results of practice in the field of education can be developed together. In this research, as an original application area, the implementation was carried out with the participation of Engineering students of a foundation university with two different groups of participants.The first of these groups consists of students who take the standardized physics laboratory course, which has a fundamental place in engineering education, and the second group consists of students from the scientific research project study group that triggers creative processes based on volunteerism. Thus, it is aimed to monitor the examples of Flipped Classroom Approach, which is realized by the integration of two different student groups in the context of formal and non-formal education of engineering education into their own xToday, the abundance of well-prepared scientific videos and the fact that they are open to internet access have led education researchers to open new application areas that are fed from these sources. It is more succesfull to complete and control distance education activities, which are enriched by using these online resources, with face-to-face lectures. For this reason, the Flipped classroom approach has become one of the preferred teaching approaches today, as it supports the use of technology, in-class interaction and allows efficient use of classroom time. This approach requires the students to come to the documents presented to them at home and to the video lessons by studying the basic theoretical knowledge at the level of comprehension and recall to be conveyed by the teacher during the lesson. Thus, it is possible to continue the lesson with activities suitable for the learning steps in the application phase in the classroom. Class time is used more efficiently by solving the problems given as homework in traditional lessons during inclass time.In order for this innovative approach to be successful, it is important that models and theories based on the results of practice in the field of education can be developed together. In this research, as an original application area, the implementation was carried out with the participation of Engineering students of a foundation university with two different groups of participants.The first of these groups consists of students who take the standardized physics laboratory course, which has a fundamental place in engineering education, and the second group consists of students from the scientific research project study group that triggers creative processes based on volunteerism. Thus, it is aimed to monitor the examples of Flipped Classroom Approach, which is realized by the integration of two different student groups in the context of formal and non-formal education of engineering education into their own xxprograms, using qualitative research techniques and to discuss the results in the theoretical field
Investigation of the flipped classroom approach with engineering students in two different groups
Keywords: Bloom taksonomisi; Bloom's taxonomy; engineering education; Fizik; Flipped Classroom approach; mühendislik eğitimi; Öğrenim ve öğretim; Physics; proje tabanlı öğrenme; project based learning; Study and teaching; Ters yüz sınıf yaklaşımı